Nivel de conocimiento y actitudes en manejo de residuos sólidos hospitalarios en internos de enfermería de la Universidad Nacional de la Amazonía Peruana Iquitos – 2024 - Gonzales Tello, Evelyn Paola (2025)
The general objective of the study was to determine the relationship between the level of knowledge and attitude about the management of hospital solid waste in Nursing Interns of the National University of the Peruvian Amazon - Iquitos 2024. Quantitative study with a non-experimental, descriptive, cross sectional and correlational design; which had a sample of 71 Nursing Interns. The technique was the interview and the instruments were the questionnaire and Likert scale (validity 94.29% and 94.29%) and (Reliability 83.4 and 81.6) The results revealed that 53.5 of the interns have low knowledge and 46.5% have high knowledge on the subject, while 69% show a favorable attitude and 31% show an unfavorable attitude towards the management of hospital solid waste. When relating the level of knowledge and attitude, 38.0% of the inmates showed a favorable attitude with an unfavorable attitude showed low knowledge. When applying the non-parametric statistical test of chi-square, a value of p=0.030 was estimated. It is concluded that the hypothesis is accepted that the level of knowledge is related to the attitude towards the management of hospital solid waste.